Achieving respectable motherhood? Exploring the impossibility of feminist and egalitarian ideologies against the everyday realities of lived Welsh working-class femininities. (November 2015) - Mannay, Dawn
Synopsis: This paper explores the tension between post-feminist discourses of freedom and the everyday negotiation of feminised identities in private and public spaces, for mothers residing in a marginalised locale in urban south Wales, UK. Applying the lens of gender to examine and foreground the place of 'choice' in mothers' lives, the paper works with visual and narrative accounts of the negotiation of acceptable motherhood. The paper argues that despite a pervasive rhetoric of agency and equality, the practice and performance of motherhood continues to operate within asymmetrical gendered and classed spaces inside the confines of respectable femininity. Challenging the concept of new motherhood, where women are led to believe that they can maintain the status of breadwinner, domestic goddess and primary care giver, the paper theorises agency as operating within the impossibility of unachievable ideals. Highlights: Focus on women's agency in maternal choice-making constituted within specific cultural, social and interpersonal contexts Drawn from study of mothers residing in a marginalised area in south Wales, UK Research methods include visual data production, narrative work and interviews. Presentation of findings includes interview data, images and poetry. Central argument that women's choices are constrained by gendered norms, local culture, patriarchy and stigma of place